INTERNALISASI KARAKTER KEMANDIRIAN PADA MATA PELAJARAN PAI (Kajian Atas Proses Pembelajaran di SMP N 2 BABAT Lamongan) - Salman Zahidi (Universitas Islam Lamongan, 2019)
One of the mandates of education is to form a superior personality, one of which is shown by the character of independence inherent in students as a result of the educational process. Thus, it is essential to research the internalization of the character of autonomy through the learning process of Islamic religious education. Research using this qualitative method aims to determine the implementation of Islamic Education learning and internalizing values. The study found, among others: 1) In the process of internalizing the teacher plays a significant role as a transmitter of values in the Islamic Education learning process; 2) The character of independence can be internalized properly, one of which is through the habituation method used by the teacher to students when Islamic Islamic Education learning takes place; 3) The actualization of the students' independence character values varies, either during the learning process or outside of school. This indicates that the internalization of values runs quite well through daily life and students' views of the values associated with the formation of an independent personality, such as having a learning ethos, self-confidence, and creativity.